Quercus ilex browse utilization by Caprini in Sierra de Cazorla and Segura (Spain) - Cuartas, P.; García-Gónzalez, R. (Plant Ecology, 1992)
The impact of domestic and wild Caprini browsing on Quercus ilex has been examined in an area of the Sierra de Cazorla. Vegetation as a herbivore food supply, herbivore feeding regime and density in the study area during six sampling periods throughout two years, has been quantified. Wild Caprini show diets similar to the available vegetation, whereas domestic Caprini tend more towards the trophic spe- cialities (browsing or grazing) of their genus. Nevertheless, this tendency was more pronounced in do- mestic goats than in sheep. A hypothetical estimate of Q. ilex intake by each species under the study conditions was carried out. It was found that domestic Caprini have a greater impact on the holm oak than wild Caprini, density and feeding-niche deviations being the main factors responsible for this sit- uation.
Keywords: Browsing; herbivore impact; quercus ilex ecosystems